Evaluation of VERIFY tool to reduce patient identification error by nurses-Quality improvement initiatives - Dr. Kripa Angeline A, Dr. Prabavathy S , Prof. Lavanya S , Mrs. Christy F, Mrs. Premalatha (South Eastern European Journal of Public Health, 2025)
Background: Identification error during specimen collection is an important aspect in patient care because these errors create a negative impact in the patient. Identification error can occur usually when specimen is from the wrong patient or mislabelled. Aims and objectives: To assess the incidence of identification error during specimen collection procedure done by nurses and to evaluate the effectiveness of VERIFY tool approach model in reducing the identification error during specimen collection. Sampling technique is purposive sampling, data collection tool followed in this study is observation checklist with 13 criteria VERIFY & PDSA model among sample size taken is 1500. Results and conclusion: With the regular sensitization sessions using “VERIFY" approach model designed based on the NABH guidelines and hospital policy; small-group and real-time education was conducted on specimen collection, extensive skill training for nurses towards the transfer specimens to pneumatic tubes. Finally, we achieved reduced the sampling error from 7 (pretest) to 1 (post test). In conclusion, regular reinforcement sessions and clinical supervision plays a major role in ensuring prevention of identification error and the safe collection of sample practices.